please show steps to solve: g(x)= (1/2) for g(x)=(x)^2 + 3(x) +4

1 Answer | Add Yours

tiburtius's profile pic

tiburtius | High School Teacher | (Level 2) Educator

Posted on

So you have `1/2=x^2+3x+4 implies x^2+3x+7/2=0`

Now you use formula for solution of quadratic equation

`x_(1,2)=(-b pm sqrt(b^2-4ac))/(2a)` where `a,` `b` and `c` are coefficients of general quadratic equation `ax^2+bx+c=0.`

Your solutions: 

` x_(1,2)=(-3 pm sqrt(3^2-4cdot7/2))/(2)=(-3 pm sqrt(-5))/(2) = `

` (-3 pm i sqrt(5))/(2) `

We’ve answered 320,040 questions. We can answer yours, too.

Ask a question